Definition of Cultural Heritage Assets - Erkinova F.F (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
This thesis explores various frameworks and perspectives that contribute to understanding cultural heritage assets, encompassing both tangible and intangible dimensions. Drawing upon international conventions such as the UNESCO World Heritage Convention and the Council of Europe's Faro Convention, as well as seminal works by scholars like David Lowenthal and Laurajane Smith, the study critically examines the evolving definitions and conceptualizations of cultural heritage.